'Where you live should not determine whether you live'. Global justice and the distribution of COVID-19 vaccines. Issue 2 (3rd April 2022) - Collste, Göran
ABSTRACT: In 2020, the world faced a new pandemic. The corona infection hit an unprepared world, and there were no medicines and no vaccines against it. Research to develop vaccines started immediately and in a remarkably short time several vaccines became available. However, despite initiatives for global equitable access to COVID-19 vaccines, vaccines have so far become accessible only to a minor part of the world population. In this article, I discuss the global distribution of COVID-19 vaccines from an ethical point of view. I reflect on what ethical principles should guide the global distribution of vaccines and what global justice and international solidarity imply for vaccine distribution and I analyse the reasons for states to prioritize their own citizens. My focus is on ethical reasons for and against 'vaccine nationalism' and 'vaccine cosmopolitanism.' My point of departure is the appeal for international solidarity from several world leaders, arguing that 'Where you live should not determine whether you live'. I discuss the COVAX initiative to enable a global vaccination and the proposal from India and South Africa to the World Trade Organization to temporarily waive patent rights for vaccines. In the final section, I argue for global vaccine sufficientarianism, which is a modified version of vaccine cosmopolitanism.